Technological Factors and Supply Chain Transparency: Role of Decision Support System - Muhammad Awais Bhatti; Nasrulla Tilabov (Decision Making: Applications in Management and Engineering, 2025)
The study objective was to formulate the impact of digital technologies, namely RFID, IOT, blockchain technology, artificial intelligence, and cybersecurity on the supply chain transparency of manufacturing SMEs. The study also tested the moderating effect of decision support system. For this purpose, quantitative cross-sectional data were collected from 305 manufacturing SMEs using a convenient sampling technique. SPSS was used for both of demographic and regression analysis. Multiple regression analysis results show that all digital technologies positively and significantly affect supply chain transparency. The moderating effect also shows that the decision support system positively strengthens the relationship between digital technologies and supply chain transparency. The study with findings contributes to the literature by confirming that digital technologies significantly enhance supply chain transparency in manufacturing SMEs. It further contributes by highlighting the moderating role of decision support systems, which strengthens the impact of these technologies. These contributions guide SME managers and policymakers to invest in integrated digital solutions for improving supply chain visibility and performance. Limitations and future directions were also discussed at the end.